De novo disruption of promoter and exon 1 of STAR gene reveals essential role for gonadal development. (13th March 2017) - Piya, Anil; Kaur, Jasmeet; Rice, Alan M; Bose, Himangshu S
Summary: Cholesterol transport into the mitochondria is required for synthesis of the first steroid, pregnenolone. Cholesterol is transported by the steroidogenic acute regulatory protein (STAR), which acts at the outer mitochondrial membrane prior to its import. Mutations in the STAR protein result in lipoid congenital adrenal hyperplasia (CAH). Although the STAR protein consists of seven exons, biochemical analysis in nonsteroidogenic COS-1 cells showed that the first two were not essential for pregnenolone synthesis. Here, we present a patient with ambiguous genitalia, salt-lossing crisis within two weeks after birth and low cortisol levels. Sequence analysis of the STAR, including the exon–intron boundaries, showed the complete deletion of exon 1 as well as more than 50 nucleotides upstream of STAR promoter. Mitochondrial protein import with the translated protein through synthesis cassette of the mutant STAR lacking exon 1 showed protein translation, but it is less likely to have synthesized without a promoter in our patient. Thus, a full-length STAR gene is necessary for physiological mitochondrial cholesterol transport in vivo . Learning points: STAR exon 1 deletion caused lipoid CAH. Exon 1 substitution does not affect biochemical activity. StAR promoter is responsible for gonadal development.